The functioning of the patient in the mental aspect and interpersonal relationship after Laryngectomy Surgery - Bury, Michał; Frąszczak, Patrycja; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2020)
Introduction. The most radical way to get rid of the cancer of the larynx is total laryngectomy. Laryngectomy involves the complete removal of the voice organ, which is the larynx, as a result of extensive laryngeal cancer categorized according to the TMN classification as T3 and T4, so this is a social problem that needs attention and should be taken into account in scientific research. Goal. Assessment of the results of the functioning of people after laryngectomy in the patient’s psyche and interpersonal relations. Material and methods. A literature review was made using PubMed, Google Scholar databases based on keywords. Results. On the percentage scale, the highest results achieved for patients without function, 63% reported physiological tests of depression, and 26% revealed mental disorders. Patients may also have anxiety disorder, phobias, panic disorder, and anxiety concentration syndromes that are able to manifest themselves in the results of stress levels. Women demonstrate that more often than men, lower initial values as a result of laryngectomy mutilation, and because of the results in the use analysis, they use substitute speech, which may sound like a male voice. When it comes to data related to the age of users, younger users (under 65 years of age) are more likely to solve mental problems. Low income, unemployment, lack of a permanent job associated with an increased risk of depression or mental treatment. Conclusions. In patients with laryngectomy after larynx cancer, they include a significant reduction in quality of life, an increase in depressive reactions, and communication difficulties in a larger group of people. This is a significant social problem that requires research.